1997
DOI: 10.1111/j.1553-2712.1997.tb03756.x
|View full text |Cite
|
Sign up to set email alerts
|

Cranial Computed Tomography in the Emergency Evaluation of Adult Patients without a Recent History of Head Trauma: A Prospective Analysis

Abstract: I ABSTRACTObjectives: To examine the pattern of nontrauma cranial CT use in an urban ED, to identify the rate of significant CT abnormalities in this setting, and to develop criteria for restricting the ordering of CT scans. Methods: A prospective, observational study of a case series of adults who underwent cranial CT scanning for nontraumatic cases was performed at the EDs of an urban teaching hospital and an affiliated community hospital with a combined annual census of 110,000. Clinically significant CT sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 20 publications
6
41
4
Order By: Relevance
“…Among the various aetiologies, neurological causes are the most common, and our findings agree with what had been reported by Kanich et al [5]. Futhermore, this has important downstream implications for triaging and cost-effective use of investigations, especially CT scan of the brain [6, 7]. …”
Section: Discussionsupporting
confidence: 91%
“…Among the various aetiologies, neurological causes are the most common, and our findings agree with what had been reported by Kanich et al [5]. Futhermore, this has important downstream implications for triaging and cost-effective use of investigations, especially CT scan of the brain [6, 7]. …”
Section: Discussionsupporting
confidence: 91%
“…Thus, reserving scans in the older population for patients with new focal neurological changes would markedly improve the clinical yield of brain CT scans. These findings reinforce those of previous studies that sought to use clinical criteria to improve the yield of brain CT scans in various populations 22–26,30 . Some physicians may lack confidence in their neurological examinations in older, hospitalized, cognitively impairedpatients, but the results of the current study indicate that brain CT scans should not be used in lieu of a neurological examination.…”
Section: Discussionsupporting
confidence: 76%
“…A more recent study by Rothrock and colleagues, which included only non-trauma patients, proved more successful in deriving criteria. 6 They found that if cranial computed tomography was restricted to only patients fulfilling any of four clinical criteria (age 60 years or older, focal neurology, headache with nausea or vomiting, altered mental status), then no significant pathology would have been missed and 28% fewer scans would have been performed.…”
mentioning
confidence: 99%